If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + -2) + 4 = 2(5x + -1) + 2 Reorder the terms: 3(-2 + 3x) + 4 = 2(5x + -1) + 2 (-2 * 3 + 3x * 3) + 4 = 2(5x + -1) + 2 (-6 + 9x) + 4 = 2(5x + -1) + 2 Reorder the terms: -6 + 4 + 9x = 2(5x + -1) + 2 Combine like terms: -6 + 4 = -2 -2 + 9x = 2(5x + -1) + 2 Reorder the terms: -2 + 9x = 2(-1 + 5x) + 2 -2 + 9x = (-1 * 2 + 5x * 2) + 2 -2 + 9x = (-2 + 10x) + 2 Reorder the terms: -2 + 9x = -2 + 2 + 10x Combine like terms: -2 + 2 = 0 -2 + 9x = 0 + 10x -2 + 9x = 10x Solving -2 + 9x = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -2 + 9x + -10x = 10x + -10x Combine like terms: 9x + -10x = -1x -2 + -1x = 10x + -10x Combine like terms: 10x + -10x = 0 -2 + -1x = 0 Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| -2x^2+12x-3= | | 4.905x^2-16x-7=0 | | 14x^2-47x-3=4 | | 3x^2-x-5= | | K/3+h/6 | | 10-12x=142+x | | (x-5)/4-(3-4x)/9=13 | | 7-8x+8=8+x | | xx-10x+25=0 | | 7a-(-b)=-6b+14 | | x^3+8x^2+24x+32=0 | | 41-4x=5x+19 | | 3a=6/7 | | (8x^2+5x+7)-(5x^2+8x-6)= | | Y-5=-4(x-6) | | 10y+6x=7 | | 3k/5=12 | | x*5+6=91 | | (6-3i)/(-8+4i) | | 4p/3=8 | | x/3=1.5/0.5 | | (x-8)/4=5 | | y=a*x+b | | 3(3x-2)+4=2(x-1)+2 | | 6f+230=500 | | 8d+5=5d+14 | | 6x+10y=7 | | (3/5)3 | | 4(x+4)(3x-6)=0 | | 0.8x-7.7=5.7 | | 1/3(x+100)=500 | | 1/x^4=256 |